Meningkatkan Kualitas Hidup Penderita HIV/AIDS Melalui Penggunaan Antiretroviral (ARV) dan Dukungan Keluarga - Saiful Batubara; Adhi Marfitra (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2020)
The damage to the immune system in people with HIV infection resulted in them being easily attacked by other diseases, especially the decrease in the quality of life of HIV-AIDS sufferers. Therefore, the purpose of this research is to know the relationship between compliance with antiretroviral use and family support in improving the quality of life of people with HIV-AIDS. For that, quantitative descriptive research with the population is the entire patient with HIV-AIDS. They undergo medical checkup at Budi Kemuliaan hospital-Batam aged between 20-35 years which amounted to 76 people and samples as many as 60 people selected using the Purposive sampling method. The results showed a significant link between compliance with the use of antiretroviral and quality of life and the relationship between the quality of life with the support of the family in HIV/AIDS patients at the Budi Kemuliaan hospital-Batam.